A compilation of North American tree provenance trials and relevant historical climate data for seven species - Clara Risk (Nature Portfolio, 2021)
Measurement(s) height • survival • phenology Technology Type(s) digital curation Sample Characteristic - Organism Pinus strobus • Pinus banksiana • Picea glauca • Picea mariana • Quercus rubra • Larix laricina • Betula alleghaniensis Sample Characteristic - Environment woodland area Sample Characteristic - Location Canada • United States of America Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13136060